Determination of Metabolic Responses of Psidium guajava L. Trees Irrigated with Polluted Water - Hemada, M.; El-Darier, S. (Innovations in Microbiology and Biotechnology Vol. 4, 2022)
The primary goal of this study was to determine the main impacts of waste water from El- Wafaeyya drain (polluted site) on some primary and secondary metabolites, nutritional and heavy metal levels,, photosynthetic pigments as well as fruit quality of seedy Psidium guajava trees irrigated with polluted water accumulated significantly higher levels of Fe, Mn, Zn, Cu, Pb, Co, and Cd than those irrigated with control water. Total photosynthetic pigments, on the other hand, were considerably lower in P. guajava leaves irrigated with contaminated water than in the control. The leaves of the control location had a higher concentration of total protein and total sugars. Tree leaves treated with contaminated water had high levels of proline, free amino acids, antioxidants, total phenolics, total flavonoids, and tannins. In the case of total alkaloids and saponins, the opposite was true. When it came to fruits, the negative impact was focused on the economic output and number of fruits rather than the weight and size of the fruits. Irrigation with polluted water, on the other hand, resulted in decreased water content, total proteins, total carbs, and vitamin A and C, but increased dietary fibres. The simultaneous use of qualitative and quantitative analyses of electrophoretic patterns makes the observations more reliable as regards the various genotoxic effects that these substances can be induced. Awareness must be taking for the application of P. guajava fruits collected from polluted locations for human uses as they are unsafe, dangerous and risky.